Cross-Linguistic Studies - Koizumi, Masatoshi (The Mouton-NINJAL Library of Linguistics [MNLL], 2023)
Issues in Japanese Psycholinguistics from Comparative Perspectives is a two-volume collection of papers on two closely related topics in Japanese psycholinguistics. Volume 1, Cross-Linguistic Studies, compares Japanese and other languages, including well-studied languages such as English, as well as lesser-studied languages such as Kaqchikel.